2006
DOI: 10.1063/1.2150602
|View full text |Cite
|
Sign up to set email alerts
|

Luminescence of bound excitons in epitaxial ZnO thin films grown by plasma-assisted molecular beam epitaxy

Abstract: Luminescence properties of ZnO films, which have been epitaxially grown on c-sapphire (0001) substrates by plasma-assisted molecular beam epitaxy, are investigated by means of different excitation sources and their measurement conditions. With the increase of measurement temperature, photoluminescence spectra clearly present, the appearance of different bound-exciton peaks (I10 line) with an abrupt increase of emission intensity at the measurement temperature of 30-50K. Hypothetical explanations on the basis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 19 publications
1
26
1
Order By: Relevance
“…We can see from the figure that the PL intensity decreases with the increase in the measuring temperature up to 35 K and then it starts to increase and shows a peak at 45 K and after that it again starts to decrease continuously for the higher temperatures. The characteristic NTQ behavior is observed in the temperature range 35-45 K. This is in agreement with our earlier results of NTQ behavior observed in the temperature range 30-50 K for un-doped ZnO thin films [20], however, the temperature range is higher when compared to the results (10-20 K) of Watanabe et al [16] for ZnO single crystals. Fig.…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…We can see from the figure that the PL intensity decreases with the increase in the measuring temperature up to 35 K and then it starts to increase and shows a peak at 45 K and after that it again starts to decrease continuously for the higher temperatures. The characteristic NTQ behavior is observed in the temperature range 35-45 K. This is in agreement with our earlier results of NTQ behavior observed in the temperature range 30-50 K for un-doped ZnO thin films [20], however, the temperature range is higher when compared to the results (10-20 K) of Watanabe et al [16] for ZnO single crystals. Fig.…”
Section: Resultssupporting
confidence: 74%
“…Meyer et al [19] explained the NTQ behavior of I 6B /I 8B donor bound exciton PL peaks at 15-20 K in ZnO crystal, through fitting an analytical equation, in terms of the emergence of excited states involving B-valence band. In a similar way, Jung et al [20] explained the enhancement of I 10 peak intensity at 40-50 K in un-doped ZnO thin film grown by plasma-assisted MBE, in terms of both the thermal- ization effect and the excitation to the vibronic/rotational resonance states or the involvement of B-valence band. Watanabe et al [16] explained, through the analytical expression, the NTQ observed in the deep level emissions, donor-acceptor pair emissions and the bound excitonic emissions in the ZnO single crystals.…”
Section: Introductionmentioning
confidence: 90%
“…An elemental Knudsen cell was used to supply zinc atoms of 6N purity, and the temperature of the cell was maintained at 355°C during deposition. Active oxygen species was generated and spread over the sapphire substrate through a radio-frequency plasma source activated at the power of 450 W. Detailed conditions for preparing and cleaning sapphire substrate were reported elsewhere [12,13]. Low-temperature buffer layer with the thickness of 15 nm was grown at 500°C, and was thermally-treated at 800°C for 30 min.…”
Section: Methodsmentioning
confidence: 99%
“…With its large exciton binding energy 60 meV, ZnO can be a prospective alternative to gallium nitride [1] as blue and UV light emitters. Different growth techniques such as metal-organic chemical vapor deposition (MOCVD), [2] sputtering, [3] pulsed laser deposition [4] and molecular beam epitaxy (MBE) [5] have been employed to produce ZnO thin films. Among them, MOCVD provides the advantage of growing high-quality films due to its versatility in controlling the various thermodynamic interactions.…”
Section: Introductionmentioning
confidence: 99%